2021
DOI: 10.1002/alr.22741
|View full text |Cite|
|
Sign up to set email alerts
|

International consensus statement on allergy and rhinology: rhinosinusitis 2021

Abstract: I. Executive Summary Background The 5 years since the publication of the first International Consensus Statement on Allergy and Rhinology: Rhinosinusitis (ICAR‐RS) has witnessed foundational progress in our understanding and treatment of rhinologic disease. These advances are reflected within the more than 40 new topics covered within the ICAR‐RS‐2021 as well as updates to the original 140 topics. This executive summary consolidates the evidence‐based findings of the document. Methods ICAR‐RS presents over 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
479
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 518 publications
(534 citation statements)
references
References 2,373 publications
(3,455 reference statements)
4
479
1
5
Order By: Relevance
“…Chronic rhinosinusitis (CRS) is persistent inflammation of the nasal and sinus mucosa lasting ≥12 weeks, accompanied by two or more nose-related symptoms such as nasal blockage and nasal discharge [ 100 , 101 ]. As with many other chronic diseases, the clinical entity of CRS is considered a disease with heterogeneity.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic rhinosinusitis (CRS) is persistent inflammation of the nasal and sinus mucosa lasting ≥12 weeks, accompanied by two or more nose-related symptoms such as nasal blockage and nasal discharge [ 100 , 101 ]. As with many other chronic diseases, the clinical entity of CRS is considered a disease with heterogeneity.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…The highest level of ARG2 expression was observed in the nonasthmatic and non-AR CRSsNP patients. The pathology of CRSsNP features cellular infiltrations of neutrophils, macrophages, and lymphocytes dominated by type 1 inflammatory cytokines [ 100 , 101 , 105 ]. It is speculated that moderate expression levels of ARG2 partially inhibit the production of NO so that it can no longer maintain its protective roles but allow an accumulation of NO in a range that is sufficient to promote type 2 inflammatory responses [ 141 ].…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…Diagnosis is made based on chronology of symptomatology and objective evidence on endoscopy or computed tomography imaging demonstrating evidence of polyposis. 3 CRSwNP is known to cause a significant burden to quality of life, 4 result in significant health care expenditures, 1 and more recently has been demonstrated to have an impact on cognitive function. [5][6][7][8] While the exact pathophysiologic mechanisms are yet to be elucidated, evidence evaluating Caucasian populations suggest an predominately type 2 inflammatory reaction and aberrant eosinophilic activation.…”
Section: Introductionmentioning
confidence: 99%
“…The 2021 International Consensus on Allergy and Rhinology Statement on Rhinosinusitis considered OCSs as a therapeutic option in CRSsNP, but the document also cited a notable lack of high-level studies assessing their efficacy. 2 A 2011 systematic review of 33 articles on OCS use in CRSsNP found that nearly all studies were level 4 or 5 evidence, affording only weak recommendations for use. 3 In a subsequent 2013 review of OCS use in the perioperative period for surgery for CRSsNP, the authors were unable to make any evidence-based recommendations, citing the absence of high-level studies on the subject.…”
mentioning
confidence: 99%
“…Although level 1 evidence supports the use of OCSs in the treatment of CRSwNP, the evidence for the use of OCSs in CRSsNP is far less substantive both in quantity and quality. The 2021 International Consensus on Allergy and Rhinology Statement on Rhinosinusitis considered OCSs as a therapeutic option in CRSsNP, but the document also cited a notable lack of high‐level studies assessing their efficacy 2 . A 2011 systematic review of 33 articles on OCS use in CRSsNP found that nearly all studies were level 4 or 5 evidence, affording only weak recommendations for use 3 .…”
mentioning
confidence: 99%